Language Teaching Methods to Students with Special Needs - Orazakynkyzy, Farida; Sakipzhamal, Uzakpayeva; Vinara, Nurlanova; Marina, Savankova; Klara, Kabylgazina (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
The idea of this research paper arose out of an awareness that students with language learning disabilities are completely ignored in the educational system and there are no special programs that cater to these students. They are placed in normal schools that are not prepared to deal with their unique difficulties. This paper, therefore, is an attempt to provide teachers with multiple-strategies models for teaching English language skills to these students at the intermediate level and beyond. More specifically, this research will help pre-and in-service teachers to: Identify effective strategies for learning and using language skills, Use multiple-strategies models for teaching language skills, Strategies for language learning and language use into regular language activities, and finally, Both the processes and products of language learning of students with learning disabilities. Thus, the target audience of this research includes pre-and in-service regular teachers, special education teachers, school psychologists, counsellors, and administrators.